Wounded Masculinity? Disability, Gender, and Canada’s Great War - Story, Eric (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2026)
War disability lies at the intersection of the wounded, injured, or sick military body and the society that gives it meaning. During the Great War of 1914–1918, more than 180,000 members of the Canadian Expeditionary Force became nonfatal casualties, compelling Canada to confront the realities of a mass disabling event. As Canadians reckoned with the scale of disability, questions of masculinity rose to the fore. War wounding was viewed simultaneously as proof of martial heroism and evidence of emasculation and dependency, leaving disabled veterans trapped between these two opposing views of military manhood. The state’s program of “vocational re-education” sought to reconcile this tension by casting work as a means to “overcome” disability and thus reclaim a masculinity deserving of returned soldiers. Disabled veterans pushed back against this premise. They exposed how the social meanings of visible and nonvisible disability shaped access to recognition, work, and masculine status in post-war Canada. While the Amputations Association of the Great War protested employment discrimination grounded in visible disability, the Tuberculous Veterans’ Association viewed their own struggles through the lens of nonvisible illness. By leveraging the apparency of war disability (or lack thereof), disabled veterans demonstrated that self-reliant masculinity was unattainable — even undesirable — so long as their disabilities were ignored.